CRISIS COMMUNICATION ANALYSIS OF PT KERETA API INDONESIA IN HANDLING PUBLIC COMPLAINTS IN MAINTAINING THE REPUTATION - Baby Poernomo; Avradya Mayagita (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
A crisis is an unexpected situation that can endanger the stability, reputation and image of an organization. This can disrupt the sustainability of a company or organization, because it has a negative impact, especially if it is not handled properly. In facing a crisis, a company can communicate with its consumers through press releases on its website or social media. This crisis communication effort is to help consumers while protecting potential victims from danger and it is hoped that this communication effort will be able to protect the company's reputation from the damage that accompanies the crisis. The research technique used in this scientific writing is documentary study, namely by researching and understanding relevant books, documents or other written sources and cases related to crisis communication. The results of this study show that with responsive action from PT KAI, the community feels cared for and gets fairly fair treatment. In this way, the existing crisis can be resolved well through appropriate communication strategies.